2017
DOI: 10.2106/jbjs.16.00166
|View full text |Cite
|
Sign up to set email alerts
|

Post-Discharge Care Duration, Charges, and Outcomes Among Medicare Patients After Primary Total Hip and Knee Arthroplasty

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 23 publications
0
38
2
Order By: Relevance
“…We found that 90.2% of patients undergoing the intensive PT protocol were discharged home, as compared to only 75.5% of patients who participated in non-intensive PT protocol (p < 0.03). Although these values are substantially higher than those reported in other studies, they demonstrate similar outcomes--rigorous postoperative PT enables patients to be discharged home sooner [19] . Additionally, Brennan et al [20] .…”
Section: Patient Demographicscontrasting
confidence: 48%
“…We found that 90.2% of patients undergoing the intensive PT protocol were discharged home, as compared to only 75.5% of patients who participated in non-intensive PT protocol (p < 0.03). Although these values are substantially higher than those reported in other studies, they demonstrate similar outcomes--rigorous postoperative PT enables patients to be discharged home sooner [19] . Additionally, Brennan et al [20] .…”
Section: Patient Demographicscontrasting
confidence: 48%
“…Previous prospective studies have also been underpowered to detect differences in complication rates between outpatient and inpatient care groups. Due to the already low rates of serious adverse events after THA, reported from 3.8% up to 8.6% in the literature, [20,35,36] sample sizes must be sufficiently large to include a sufficient number of events to support clinical conclusions. Our protocol will be the first adequately powered prospective study to evaluate the safety of outpatient THA.…”
Section: Discussionmentioning
confidence: 99%
“…6,12 Discharging patients home instead of PAC inpatient facilities can save up to US$14,000 per EOC. 13 In fact, it has been demonstrated that extending a patient's hospital stay by an additional 5.2 days in an effort to discharge the patient directly home resulted in reduced overall costs and superior outcomes than THA recipients who were discharged to a PAC facility. 14 Despite these advantages, it is important to properly assess which patients will need postacute inpatient care.…”
Section: Discussionmentioning
confidence: 99%